Studi Evaluasi Pelayanan Sistem Administrasi Manunggal Di Bawah Satu Atap Online Di Kantor Samsat Pekanbaru Selatan - Fardina, Ari; Munaf, Yusri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
The research on to evaluation about implementation of one stop service online system about to certificate of motor vehicles and motor vehicle tax services and more barrier factors in implementated. The indicators value include is procedure, finishing time limited, tarif/cost services, product, fasilities and competention. Type of research at one stop service south Pekanbaru office is descriptive surveys that questioner list priority as instrument taking data to analisys empiris condition and obyectivity in the location research. Two have population group and sample is 101 empower birocrate and civilitization that uncountable about 300/days to visited one stop service south Pekanbaru office. The civilization on the research is subject of tax that want to certificate of motor vehicles and motor vehicle tax services. Totality sample of two population group is 50 and 200 used proportionate stratified random sampling. Data on research is primer data by questioner list and interviews and secunder data used observation technics, and such analisys data used frecuence of table instruments. Conclution from research on Evaluation Studies Samsat Online System at one stop service south Pekanbaru Office is interval range “good enough”. Barrier factors intern is throuble computer, throuble internet connectivity, and uncoorditination works intuitions one stop service that not synergy between institute policy. Barrier factors extern is form administrative is not completed, and the custumer is unknown to Samsat online sytem. The recomedation is that first, make to practice procedure online system and bangking online system to pay tax.